Linear convergence of the Douglas–Rachford method for two closed sets. (1st February 2016) - Phan, Hung M.
Abstract : In this paper, we investigate the Douglas–Rachford method (DR) for two closed (possibly nonconvex) sets in Euclidean spaces. We show that under certain regularity conditions, the DR converges locally with -linear rate. In convex settings, we prove that the linear convergence is global. Our study recovers recent results on the same topic.